The association between expressive suppression and anxiety in Chinese left-behind children in middle school: serial mediation roles of psychological resilience and self-esteem - Tingting Qu; Qiwen Gu; Huan Yang; Chennan Wang; Yuping Cao (BMC Psychiatry, 2024)
Abstract Background Left-behind children (LBC) have become a special population to be concerned due to the negative consequences of parental absence during their physical and psychological development in China. Expressive suppression (ES) is a response-focused emotion regulation and may be frequently used by LBC to suppress their emotions resulting in different forms of internalizing problems. The objective of the present study was to investigate the role of ES as an emotion regulation strategy on anxiety in Chinese left-behind children in middle school (LBC-MS) by considering the mediating role(s) of psychological resilience and self-esteem. Methods 820 middle school students aged between 12 and 17 years from a middle school in Xiangtan, Hunan Province, participated in the study. Screen for Child Anxiety Related Emotional Disorders (SCARED), Emotion Regulation Questionnaire (ERQ), Resilience Scale for Chinese Adolescents (RSCA), and Rosenberg Self-Esteem Scale (SES) were administered. Variables measured using the above scales in left-behind children in middle school (LBC-MS) and non-left-behind children in middle school (non-LBC-MS) were compared, and descriptive statistics were used to present the overall characteristics. Then the PROCESS macro of SPSS was used to conduct regression-based statistical mediation for the data of 211 left-behind children. Results This study revealed that LBC-MS had higher anxiety and ES scores and lower psychological resilience and self-esteem scores than non-LBC-MS (Ps < 0.01). ES was found positively associated with anxiety in LBC-MS and negatively associated with psychological resilience and self-esteem (Ps < 0.05 − 0.01). Specifically, both psychological resilience and self-esteem significantly mediated the association between ES and anxiety, accounting for 7.50% and 10.68%, respectively, of the total associations. Moreover, psychological resilience and self-esteem had a chain mediating effect between ES and anxiety in LBC-MS. Conclusion The findings indicated that LBC-MS in China may frequently engage in the use of ES which correlated with higher level of anxiety. Psychological interventions should be dedicated to this underserved group. Intervention approaches that improve emotion regulation strategies (i.e., decrease the use of ES) and increase psychological resilience and self-esteem may help to alleviate anxiety in LBC-MS.